Deletion of autophagy related, ATG1 and F‐box motif encoding YDR131C, together, lead to synthetic growth defects and flocculation behavior in Saccharomyces cerevisiae. Issue 7 (6th April 2022) - Shoket, Heena; Parvez, Sadia; Sharma, Meenu; Pandita, Monika; Sharma, Vishali; Kumar, Prabhat; Bairwa, Narendra K.
Abstract: Ubiquitin proteasome system (UPS) and autophagy both pathways are involved in clearing the nonessential cellular components and also crosstalk during cellular response to normal and stress conditions. The F‐box motif proteins constitute the SCF‐E3 ligase complex of the UPS pathway in Saccharomyces cerevisiae and are involved in the substrate recruitment for ubiquitination. The ATG1 encoded Atg1p, a conserved serine‐threonine kinase is crucial for the autophagy process. Here in this study, we report that loss of F‐box motif encoding YDR131C and ATG 1 together results in growth defects, floc formation, sensitivity to hydroxyurea, methyl methanesulfonate, and hydrogen peroxide. Both the genes also interact with the flocculation‐related genes (FLO) and associate with gene ontology terms "ubiquitin‐protein transferase activity" and "cellular catabolic process." Based on in silico analysis and experimental evidence we conclude that YDR131C and ATG1 function in parallel pathways to regulate the growth, flocculation, and stress response.